Does dietary diversity reduce the risk of obesity? Empirical evidence from rural school children in China - Chang Tao; Qiran Zhao; Thomas Glauben; Yanjun Ren (International Journal of Environmental Research and Public Health, 2020)
Childhood and adolescence overweight and obesity have implications for both health consequences and economic burden. Although it has been an emerging public health problem for primary school children in rural China and the importance of the diet–health link has been stressed for many years, rigorous analysis of the dietary diversity and obesity among children is rare. To clarify this issue, this study provides a better understanding of the functional linkage between dietary diversity and obesity by analyzing data from nearly 8500 rural primary students (aged from 10 to 13 years old) covering three provinces in China. Our estimation results show that there is a significantly negative correlation between dietary diversity and the probability of being overweight among primary students. In particular, for subgroups with higher dietary diversity, the negative correlation between dietary diversity and the incidence of overweight or obesity is stronger, and the absolute value of the coefficient is greater. The results also suggest that the increase in the consumption frequency of all dietary categories can significantly lead to a lower proportion of overweight. Thus, we conclude that higher dietary diversity can help to lower the risk of overweight and obesity among primary school children, presumably through increasing the daily frequency of food intakes and developing a more diverse dietary pattern.
Keywords: 300; dietary diversity; overweight; obesity; rural China